FeVO4 nanowires for efficient photocatalytic CO2 reduction. Issue 10 (13th April 2022) - Li, Yang; Zeng, Zhaojian; Chen, Yong; Zhang, Yuanming; Wang, Wenjing; Xu, Xiaoming; Du, Mengyang; Li, Zhaosheng; Zou, Zhigang
Abstract : Band structures of the FeVO4 semiconductor were investigated by first-principles calculations, and FeVO4 nanowires can greatly improve the performance of photocatalytic CO2 reduction. Abstract : Photocatalytic CO2 reduction is of great significance for alleviating environmental pollution and energy shortages. Double transition metal oxide semiconductors are a commonly used material library in the field of photocatalysis. However, there are a few reports about bimetallic oxide photocatalysts for CO2 reduction by using solar energy. Here, we report a bimetallic oxide catalyst FeVO4 with durable photocatalytic CO2 reduction activity. Band structures of the FeVO4 semiconductor were investigated by first-principles calculations. FeVO4 is an indirect band gap semiconductor with a band gap of approximately 2.25 eV, the absorption edge of which can reach 550 nm. The morphology of the FeVO4 catalyst can be tuned by using various synthesis methods. The FeVO4 catalyst with a nanowire structure was prepared by a hydrothermal method. The FeVO4 nanowires have a larger specific surface area and more oxygen vacancies than FeVO4 particle samples synthesized by solid-phase sintering. Exposure to numerous basic active sites facilitates the adsorption and activation of CO2, thereby greatly improving the catalytic performance of FeVO4 nanowires for CO2 reduction.